Transmembrane adaptor protein PAG/CBP is involved in both positive and negative regulation of mast cell signaling - Draberova, Lubica; Bugajev, Viktor; Potuckova, Lucie; Halova, Ivana; Bambouskova, Monika; Polakovicova, Iva; Xavier, Ramnik J; Seed, Brian; Draber, Petr (Molecular and cellular biology, 2014)
The transmembrane adaptor protein PAG/CBP (here, PAG) is expressed in multiple cell types. Tyrosine-phosphorylated PAG serves as an anchor for C-terminal SRC kinase, an inhibitor of SRC-family kinases. The role of PAG as a negative regulator of immunoreceptor signaling has been examined in several model systems, but no functions in vivo have been determined. Here, we examined the activation of bone marrow-derived mast cells (BMMCs) with PAG knockout and PAG knockdown and the corresponding controls. Our data show that PAG-deficient BMMCs exhibit impaired antigen-induced degranulation, extracellular calcium uptake, tyrosine phosphorylation of several key signaling proteins (including the high-affinity IgE receptor subunits, spleen tyrosine kinase, and phospholipase C), production of several cytokines and chemokines, and chemotaxis. The enzymatic activities of the LYN and FYN kinases were increased in nonactivated cells, suggesting the involvement of a LYN- and/or a FYN-dependent negative regulatory loop. When BMMCs from PAG-knockout mice were activated via the KIT receptor, enhanced degranulation and tyrosine phosphorylation of the receptor were observed. In vivo experiments showed that PAG is a positive regulator of passive systemic anaphylaxis. The combined data indicate that PAG can function as both a positive and a negative regulator of mast cell signaling, depending upon the signaling pathway involved.
Keywords: Cell Degranulation; Mice, Inbred C57BL; Mast Cells; Bone Marrow Cells; vápník; zvířata; Phosphorylation; Receptors, IgE; Signal Transduction; kinasa Syk; Protein-Tyrosine Kinases; Type C Phospholipases; mastocyty; tyrosinkinasy; RNA Interference; signální transdukce; Proto-Oncogene Proteins c-fyn; Mice; RNA interference; myši knockoutované; Animals; Proto-Oncogene Proteins c-kit; protoonkogenní proteiny c-kit; fosfoproteiny; Anaphylaxis; CSK Tyrosine-Protein Kinase; intracelulární signální peptidy a proteiny; receptory IgE; skupina kinas odvozených od src-genu; C-terminální Src kinasa; Phosphoproteins; RNA, Small Interfering; fosfolipasy typu C; degranulace buněk; src-Family Kinases; Calcium; fosforylace; anafylaxe; malá interferující RNA; Mice, Knockout; buňky kostní dřeně; membránové proteiny; Intracellular Signaling Peptides and Proteins; Syk Kinase; Membrane Proteins; myši; myši inbrední C57BL; protoonkogenní proteiny c-fyn